HUBUNGAN MOTIVASI KERJA DENGAN KINERJA PEGAWAI DI KANTOR CAMAT ONOHAZUMBA KABUPATEN NIAS SELATAN - Waruwu, Risman (Universitas Nias Raya, 2025)
This research aims to find out how motivation of work is linked to the performance of officials in the Onohazumba Camat Office of Southern Nias district. The type of research used in this research is quantitative research that is causal. The sample determination technique used is non probability sampling by saturating. Population methods in this study, that is, all of the staff at Camat Onohazumba Office consisted of 32 people. Sample methods in this study, that is, all of the staff at Camat Onohazumba Office consisted of 32 people. The results of this study show that there is a relationship between motivation of work and the performance of staff at the Camat onohazumba office in Southern Nias district. The suggestion in this study is that, in order for the employee to produce a better job, then the superior should give special attention to the staff who have a good performance so that he gets more enthusiastic in the work.